(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Review of: Nicola Brandt, Landscapes between Then and Now. Recent Histories in Southern African Photography, Performance and Video Art, Abingdon, Routledge, Taylor & Francis Group, 2020.